Monitoring silver diamine fluoride application with optical coherence tomography and thermal imaging: An in vitro proof of concept study. Issue 5 (25th February 2022) - Abdelaziz, Marwa; Yang, Vincent; Chang, Nai‐Yuan Nicholas; Darling, Cynthia; Fried, William; Seto, Jong; Fried, Daniel
Abstract: Objectives: The purpose of this study was to show that optical coherence tomography (OCT) and thermal imaging can be used to monitor changes in the structure and activity of caries lesions over time after treatment with silver diamine fluoride (SDF). Methods: Artificial caries lesions were formed on enamel and dentin bovine blocks. Each block was partitioned into five windows with the central three windows exposed to a demineralization solution to create lesions: one sound window served as a sound control (SC), one sound window was exposed to SDF to serve as a test control (SCT), one lesion window served as a lesion control (LC), one lesion window received one application of SDF (L1), while the other lesion window received two applications of SDF (L2). Each window was scanned using OCT before SDF application, and every week subsequently, for 12 weeks after initial SDF treatment. Changes in the mean intensity and the width of the peak of increased reflectivity due to the lesion and SDF along with the intensity at a depth of 180 µm from the surface representing optical penetration through the lesion were monitored. Changes in the heat lost, Δ Q (temperature integrated over time) of each window during drying with air were also monitored using a thermal imaging camera. Transverse microradiography (TMR), and high‐resolution microscopy were also used for the analysis of selected samples. Results: The reflectivity and optical penetration of sound and lesion areas of enamel and dentin manifested significant changes in OCT images after SDF application. Thermal imaging showed significant differences in Δ Q indicative of permeability changes in the sound and lesion areas of enamel and dentin after SDF application.